The Usefulness of Management Accounting Information: Users’ Attitudes - Gaidienė, Zina; Skyrius, Rimvydas (Ekonomika, 2006)
During the years of Lithuanian economic independence, much emphasis is laid on financial accounting and auditing, whereas management accounting has been languishing in the background. This paper investigates the role and development of management accounting and the usefulness of its information perceived by managers. The management accounting system is characterized in terms of information. These characteristics are: scope, timeliness, the level of aggregation, and information which assists integration. Empirical support for the relationship between the features of management information and its perceived usefulness is provided using data gathered from questionnaires and interviews. The search for usefulness of management accounting information was guided by the accounting research literature. The goal has been to determine what features of information are recognized by managers and accountants as useful. The results of analysis have shown that all interviewed managers perceived management accounting (economic and non-economic) information as useful. However, the level of their scores has been higher than that of accountants. There had been no comprehensive study involving the evaluation of usefulness of accounting information by Lithuanian managers. The present study has been undertaken to learn more about how Lithuanian managers perceive the usefulness of management accounting information. This was the principal objective of this research. Since managers’satisfaction with the accounting system could be highly biased, the next objective was to determine whether accountants perceived the same features of information as useful. The third objective of this study was to review the possibilities for the development of management accounting systems. Thus, the purpose of this paper was to examine the perception of usefulness of accounting information by its suppliers and users. The paper proceeds as follows. We describe management accounting, its role and development. We provide a framework for the survey based on a review of the extensive literature on research published by foreign management accounting journals during the period 1980-2005, including Accounting, Organizations and Society. The Accounting Review, Contemporary Accounting Research, Journal of Accounting and Economics, Journal of Management Accounting Research, Strategic Finance, Business and Finance History. Cost Accounting Magazine, Management Accounting Quarterly. A survey and its statistical analysis are presented. The final section contains conclusions.